Peningkatan Kuat Tekan dan Kuat Lentur Beton Dengan Variasi Penambahan Serat Daun Nanas - Gusneli Yanti; Z. Zainuri; Shanti Wahyuni Megasari (Diponegoro University, 2019)
Concrete is a building material that is widely used, because this material is strong against the press, can be easily formed to suit the needs. In the other side, has a weakness against bending and has brittle properties, so that a method is needed to correct this weakness. One effort to increase the tensile strength of concrete is done by adding fiber so that it becomes a composite material, namely concrete and fiber. This research aims to improve compressive strength and flexural concrete by adding fiber with variations of 0%, 1%, 3%, 5%, and 7% on the weight of cement on the concrete quality of K-225. The concrete design uses the Department of Environment (DOE) method, with cylinder molds with a size of 150 mm x 300 mm. The number of samples in each variation were 3 specimens and a total sample of 30 specimens. Testing results show that the highest compressive strength and flexural strength in mixed variations with an additional pineapple leaf fiber of 5% with an average compressive strength of 267.00 kg / cm2 and average flexural strength of 41.61 kg / cm2.